The learning subject in a medicine career: the medical health care process, the clinical method - Luis Alberto Corona Martínez (Medisur)
The present paper is based on the need to incorporate the learning subject category to the professional practitioner model contained in the curriculum of the medicine career. This category should represent the fundamental activity of physicians in their professional work. The analysis of functions performed by these professionals allows identifying assistance and the process generated by it: the process of medical health care, as the learning subject for any medicine student. Identifying the learning subject as a concept or category to use in the professional practitioner model, and the accuracy of that learning subject for the medical student, that is, the process of medical health care, provides didactically valuable input due to its undeniable educational value in guiding the teaching-learning process both, for students and teachers.